Outcomes for Patients Who Contact the Emergency Ambulance Service and Are Not Transported to the Emergency Department: A Data Linkage Study. (4th July 2019) - Coster, Joanne; O'Cathain, Alicia; Jacques, Richard; Crum, Annabel; Siriwardena, A. Niroshan; Turner, Janette
Abstract: Objectives : Emergency ambulance services do not transport all patients to hospital. International literature reports non-transport rates ranging from 3.7–93.7%. In 2017, 38% of the 11 million calls received by ambulance services in England were attended by ambulance but not transported to an Emergency Department (ED). A further 10% received clinical advice over the telephone. Little is known about what happens to patients following a non-transport decision. We aimed to investigate what happens to patients following an emergency ambulance telephone call that resulted in a non-transport decision, using a linked routine data-set.Methods : Six-months individual patient level data from one ambulance service in England, linked with Hospital Episode Statistics and national mortality data, were used to identify subsequent health events (ambulance re-contact, ED attendance, hospital admission, death) within 3 days (primary analysis) and 7 days (secondary analysis) of an ambulance call ending in non-transport to hospital. Non-clinical staff used a priority dispatch system e.g. Medical Priority Dispatch System to prioritize calls for ambulance dispatch. Non-transport to ED was determined by ambulance crew members at scene or clinicians at the emergency operating center when an ambulance was not dispatched (telephone advice).Results : The data linkage rate was 85% for patients who were discharged at scene (43, 108/50, 894). After removal of deaths associated with end of life care ( N = 312), 9% (3, 861/42, 796) re-contacted the ambulance service, 12.6% (5, 412/42, 796) attended ED, 6.3% (2, 694/42, 796) were admitted to hospital, and 0.3% (129/42, 796) died within 3 days of the call. Rates were higher for events occurring within 7 days. For example, 12% re-contacted the ambulance service, 16.1% attended ED, 9.3% were admitted to hospital, and 0.5% died. The linkage rate for telephone advice calls was low because ambulance services record less information about these patients (24% 2, 514/10, 634). A sensitivity analysis identified a range of subsequent event rates: 2.5–10.5% of patients were admitted to hospital and 0.06–0.24% of patient died within 3 days of the call.Conclusions : Most non-transported patients did not have subsequent health events. Deaths after non-transport are an infrequent event that could be selected for more detailed review of individual cases, to facilitate learning and improvement.